Spirometry in Primary Care: An Analysis of Spirometry Test Quality in a Regional Primary Care Asthma Program - Christopher J Licskai; Todd W Sands; Lisa Paolatto; Ivan Nicoletti; Madonna Ferrone (Canadian Respiratory Journal)
BACKGROUND: Primary care office spirometry can improve access to testing and concordance between clinical practice and asthma guidelines. Compliance with test quality standards is essential to implementation.